Psychological Wellbeing of Adolescents in Disadvantaged Communities: The Need for Strength-Based Approaches - Treesa Pulickal (Journal of Social Work Education and Practice, 2020)
Contextual factors play a decisive role in the wellbeing of adolescents. Relationships and interactions in the community in which they live influence their psychological wellbeing. In this context, understanding the psychological wellbeing of adolescents in disadvantaged communities needs special attention as they face severe adversities in this regard. This study was conducted in the State of Kerala in India, which had made exceptional progress in Human Development by the 1980s itself, as reflected in its social indicators. All sections of the population have not benefited equally from this development process. Among the many vulnerable sections in Kerala, one of the most neglected is the population in the disadvantaged communities. ​ The present study is a quantitative enquiry of the psychological wellbeing of adolescents in disadvantaged communities of Kerala. Sixty adolescents of age group between 10 and 19 were randomly selected from five communities, which were declared as slums or slum-like areas by Municipal Corporations in Kerala. It was found that there is a significant relationship between community disadvantage and adolescents' psychological wellbeing that include autonomy, environmental mastery, personal growth, positive relationship with others, purpose in life and self-acceptance. The need for Strengths-based approaches focused on the inherent strengths of children, families and communities, to improve the mental health and wellbeing of young children is also discussed in this paper.